2017
DOI: 10.1037/rep0000119
|View full text |Cite
|
Sign up to set email alerts
|

Job matching: An interdisciplinary scoping study with implications for vocational rehabilitation counseling.

Abstract: Unlike in IOP and VP, there is a dearth of JM research in the RTW context. Integrating the broad organizational and occupational JM knowledge from IOP and VP with the biopsychosocial framework of RTW could provide a sound basis for developing JM applications in vocational rehabilitation counseling that promote sustainable work reintegration of persons with disabilities. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 270 publications
(143 reference statements)
1
11
0
3
Order By: Relevance
“…Establishing a suitable vocational solution requires the determination of occupations whose demands and characteristics match an individual's capabilities and characteristics. 17 By providing general information on the key demands and characteristics across the most prevalent occupations of individuals with different SCI severities, our study supports the initial screening towards a first selection of well-matching occupations in vocational guidance. After completing such an initial screening, vocational counselors should evaluate on an individual level how well the demands and characteristics of these preselected occupations match with the client's capabilities and characteristics.…”
Section: Practical Implicationssupporting
confidence: 56%
See 2 more Smart Citations
“…Establishing a suitable vocational solution requires the determination of occupations whose demands and characteristics match an individual's capabilities and characteristics. 17 By providing general information on the key demands and characteristics across the most prevalent occupations of individuals with different SCI severities, our study supports the initial screening towards a first selection of well-matching occupations in vocational guidance. After completing such an initial screening, vocational counselors should evaluate on an individual level how well the demands and characteristics of these preselected occupations match with the client's capabilities and characteristics.…”
Section: Practical Implicationssupporting
confidence: 56%
“…By specifying the particular demands and characteristics of an occupation, the O*NET descriptors identified in our study can serve as a basis for developing standardized job matching profiles for vocational guidance. Returning to a wellmatched occupation after injury could help persons with SCI to realize their vocational potential, and also promote their job satisfaction, job performance and healthy employment, 17 all of which are key indicators for a sustainable return to work. To truly establish the potential of O*NET-based job matching profiles, however, both their applicability in vocational guidance and their contribution toward a sustainable return to work should be tested in future research.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the overall focus on work participation, a challenge is to translate the outcomes of such broader work capacity assessments to the type of support needed for a person to use his/ her remaining work capacity in another job [9]. This process of finding a matching job for persons with disabilities requires compatibility between an individual's capacities, characteristics and health-condition specific needs, and the demands and characteristics of his or her occupation, job and workplace [10,11]. N€ utzi et al [11] describe three overarching matching domains or levels of job matching: (1) fit between rather stable attributes (such as vocational interest, values or abilities) and the corresponding characteristics of occupations;…”
Section: Introductionmentioning
confidence: 99%
“…N€ utzi et al advocate the use of an interdisciplinary approach to job matching, incorporating a biopsychosocial framework and considering the needs and limitations of persons with disabilities. Such a comprehensive approach will allow for indicating mismatches on several dimensions, thus facilitating the intervention planning of professionals [11]. A recent study showed that workers with disabilities who are mismatched have worse work-related outcomes than those with good job matches, especially in the case of lower educated workers [3].…”
Section: Introductionmentioning
confidence: 99%